Places in Common: Exploring the Economic Geography of the Food Systems through the Case of Spain's Dairy Chain (1950s-Present) - Collantes, Fernando (TSEG - The Low Countries Journal of Social and Economic History, 2016)
How has the geography of the food system evolved as a result of the rise of a modern food processing industry? Have the geographies of farming and food processing conditioned each other strongly? Or, on the contrary, has there been a division of labour between farming regions and food processing regions? This article investigates this question through the case of Spain’s dairy chain between the 1950s and the present. The Atlantic regions in the north of the country had a clear environmental advantage for the development of dairy farming and were leaders in both dairy farming and dairy processing. However, the evolution of economic policy, consumption patterns and the cost structure of processors also had an impact on the economic geography of the chain.